Sustainable Development : Engineering, Construction and Architectural Management - Volume 14, Issue 6. - Dulaimi, Mohammed (Emerald Group Pub., 2006)
This ECAM e-book publishes seven selected papers from The Joint Conference on Construction, Culture, Innovation and Management held in Dubai from 26 to 29 November. The overwhelming theme of this issue is culture and the cultural issues affecting construction management which is reinforced by the international group of authors contributing to the issue. The recurrent theme throughout is trust as it is apparent that this is the current unsolved research area in construction management.